The trends of employees of the Supreme Council for youth forward novelty and its impacts on the social, economic and political life of youth - S.K. Jaradat, Dr. Mohammad (IJRDO - Journal of Social Science and Humanities Research, 2016)
This study aimed for realizing the trends of employees of the Supreme Council for youth forward novelty and its impacts on the social, economic and political life of youth. It was applied on (1110) employees, "185" of whom were selected randomly to fill the study application. The mechanism of such study was prepared and submitted to a number of arbitrators specialized in this domain, and the reliability of it was calculated be the repetition method to reach 0.85.